Influence of Brand Image, Price Perception, and Social Media Marketing on Buying Interest in Popits Sandals Among Denpasar Residents - Siswanto, Katheline Pratiwi; Sumerta, I Komang (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2024)
High consumer buying interest will increase consumer interest in making purchases on Popits brand flip-flops in this case influenced by brand image, price perception and social media marketing. In this case, the Popits brand flip-flops experienced problems in the level of interest in purchasing due to the lack of diversity of product variants, different price perceptions between consumers and the number of consumers who did not know the content presented by Popits from social1media. The0purpose0of0this study0was0to0determine0the brand0image, price0perception and social0media0marketing on the interest0in buying0flip-flops with the Popits brand in the people of0Denpasar. The0population0in0this study were all potential consumers of Popits brand flip-flops in the city0of Denpasar. The sample became decided the usage of purposive random sampling approach, with 120 respondents. The records series approach used is a questionnaire. The records evaluation strategies used are Classical Assumption test, more than one Linear Regression evaluation, Coefficient0of dedication,0F-test,0t-test. The outcomes of this have a look at suggest that understanding the emblem picture, rate notion and social1media1marketing concurrently affect the hobby in buying turn-flops with the Popits logo. Based at the effects of the partial check, it could be seen that understanding logo photo, price belief and social1media advertising and marketing have a wonderful and large impact on buying interest in Popits emblem turn-flops. The belief of this look at is that the higher the logo picture, rate notion and social1media advertising, the interest in buying Popits1brand1flip-flops will boom.